2016
DOI: 10.18632/oncotarget.6911
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymph node ratio in stage IIIC epithelial ovarian cancer with node-positive in a SEER population-based study

Abstract: To assess the prognostic value of the lymph node ratio (LNR) in patients with stage IIIC epithelial ovarian cancer (EOC) with node-positive in a Surveillance, Epidemiology, and End Results (SEER) population-based study. Data of patients were obtained from the SEER database from 1990 to 2012, and analyzed using Kaplan-Meier survival methods and Cox regression proportional hazard model. The prognostic value of the LNR on cause-specific survival (CSS) and overall survival (OS) were calculated. A total of 5,926 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…LNR, combining positive lymph nodes and resected number, should be utilized to reduce the potential bias. 18 In stage IIIC ovarian cancer patients with lymphadenectomy, increasing LNR leads to significantly decreased OS, 18,35 which was similar to the results of our study. In our study, we demonstrated that, in FIGO stage III patients, LNR within 0 to ≤40% group had survival advantage over LNR more than 40% group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…LNR, combining positive lymph nodes and resected number, should be utilized to reduce the potential bias. 18 In stage IIIC ovarian cancer patients with lymphadenectomy, increasing LNR leads to significantly decreased OS, 18,35 which was similar to the results of our study. In our study, we demonstrated that, in FIGO stage III patients, LNR within 0 to ≤40% group had survival advantage over LNR more than 40% group.…”
Section: Discussionsupporting
confidence: 89%
“…In FIGO stage I, a large number of resected lymph nodes did not represent a better outcome. The patients with [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] RLNs have the best prognosis. When RLNs numbered more than 30, the survival rate decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the theoretical aim of LND in surgery is at detecting positive lymph nodes to remove microscopic metastasis, we furtherly explored the survival impact of removing pathological lymphatic metastasis in patients with no gross residual disease. Published studies evaluated the lymph metastasis status with the number of positive nodes, LNR, or log odds of positive lymph nodes (LODDS) and reported that the extent of lymph node involvement was a prognostic factor in OC (26)(27)(28)(29). In RCT (20), the researchers did not further analysis the patients who was found pathologic positive lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 41,000 cases and a estimated 27,000 women die from this disease every year in China [4]. The peak incidence of EOC is over 70 years of age, and these elderly patients account for approximately two-thirds of cancer-related deaths [5][6][7][8][9]. With the improvement in population age and life expectancy, the increasing number of patients has altered the demographics of EOC.…”
Section: Introductionmentioning
confidence: 99%